2012
DOI: 10.1007/s00703-012-0227-3
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations of saltation activity at Tazhong: the hinterland of Taklimakan Desert

Abstract: The Taklimakan Desert of China is a region of frequent sandstorms and, thus, is a major sand and dust source area. Tazhong, a small mining village, is located near the center of the Taklimakan Desert at a distance of 220 km from the desert margins. Near Tazhong, we conducted a 2-year field investigation designed to monitor the diurnal variation of saltation activity using fast-responding piezoelectric saltation sensors (Sensits). Results suggest that saltation activity tends to occur more frequently during day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…In terms of the data source, an uncertainty analysis of five flux observation sites was conducted in the current study (Figure 9a). The Tazhong station had the largest RU, possibly because it was located in an extremely arid area and was greatly influenced by the climate factors such as rainfall and temperature [60], which is important given that the meteorological conditions are the main factors affecting the change in NPP [99][100][101]. When using multiple models, the differences in the structures of the models used in different studies have a certain impact on the estimation of NPP [102,103].…”
Section: Quantifiable Sources Of Uncertaintymentioning
confidence: 99%
“…In terms of the data source, an uncertainty analysis of five flux observation sites was conducted in the current study (Figure 9a). The Tazhong station had the largest RU, possibly because it was located in an extremely arid area and was greatly influenced by the climate factors such as rainfall and temperature [60], which is important given that the meteorological conditions are the main factors affecting the change in NPP [99][100][101]. When using multiple models, the differences in the structures of the models used in different studies have a certain impact on the estimation of NPP [102,103].…”
Section: Quantifiable Sources Of Uncertaintymentioning
confidence: 99%
“…However, the intermittency of aeolian saltation over gobi is also influenced by sand availability. Results in this study revealed that AP was smaller than 1 throughout the entire measurement period, partly because the sand supply in the gobi area is limited; comparatively, continuous saltation on sand surfaces is common (e.g., Yang et al, 2013), in which the relatively less limited sand supply usually plays an important role. Our study revealed that the saltation threshold U t was mainly affected by the transport intensity AP.…”
Section: Intermittency and Saltation Thresholdmentioning
confidence: 68%
“…Hourly mean is calculated from in situ observation with a temporal resolution of 5 min. [70]. The stable boundary layer at nighttime was approximately 400-800 m thick, and the residual mixing layer above it could reach a thickness of over 3000 m, with a supernormal thickness existing over the Taklimakan Desert during the summer when it rained [71].…”
Section: Dust Optical Properties From Modis and Ground-based Sun Phot...mentioning
confidence: 96%